Européanisation au XXe siècle un regard historique = Europeanisation in the 20th century - Osmont, Matthieu (Euroclio, 2012)
Historicising Europeanisation : An Introduction / Reiner Marcowitz -- Actors and Discourses of Europeanisation/Acteurs et discours d'européanisation -- Europeanisation and Modernity during the "Second Thirty Years War" : Discourses on Europe in British and American Print Media, 1914-1945 / Florian Greiner -- Élites conservatrices et politique extérieure privée en Europe de l'Ouest après la Seconde Guerre mondiale / Johannes Groámann -- Europeanising Whitehall? The British Civil Service and Europe, 1957-1972 / Thomas Raineau -- Vers la conclusion de conventions salariales européennes? Le cas de l'industrie chimique en Europe du Nord-Ouest, 1960-1980 / Remi Devemy -- Europeanising science and art/L'Europe par la science et les arts -- Castle Studies in Germany and France : From the "Struggle for the Rhine" to a European Scientific Community / Fabian Link -- Europeanising Impacts from the Colonies : European Campaigns against Sleeping Sickness, 1900-1914 / Sarah Ehlers -- European Aesthetic Convergence and the Common Market : A Case Study of Cold War East and West Germany / Katrin Schreiter -- Problems as Stimula/L'Europe, solution : des problèmes concrets -- Labour Migration within the European Economic Community: Debates and Policies in the Destination Cities / Olga Sparschuh -- Le "Waldsterben" : Convergences et divergences franco-allemandes face à un problème écologique / Laurent Schmit -- Containerisation of Rotterdam's Hinterland, 1966-2010 : A stimulus to European Economic Integration? / Klara Paardenkooper